Impacto do clima organizacional na intenção de rotatividade em call centers - Castro, Patrícia Mendes (2009)
The main objective of this study was to investigate the predictable relationships between the factors of organizational climate and turn over intention. It was developed with 333 call center’s operators of three companies of charging section in Fortaleza (Ceará). The obtained answers were codified in a spreadsheet of the SPSS program and submitted to different methods of descriptive statistics. The results of the analyses of regression for the general sample revealed that the model explained the amount of employees (18%) that intended to change for another company of other segment and the amount (20%) of the intention of changing for other call centers. The variables “identification with the position” and “identification with the tele-charging service” were significantly responsible for the intention of changing for a company of another segment. On the other hand, the variables “identification with the position”, technical orientation offered by supervisors”, socio-afective support” and “satisfaction with the organization” were significantly responsible for the intention to change to an organization of other segment. It is important to point out that the variables that more interfered in the intention to change for a company of another segment and for the intention of changing for another call center were those belonging to the group of variables of behavioral factor. The conclusions of the study point to the necessity of further studies with similar methods that can increase the knowledge about the relationship between the considered variables in other organizational realities.